An experimental study on the effect of isoniazid on the efficacy, plasma concentration and toxicity of paracetamol in Albino rats - Dahiya, Navdeep; Sharma, Sushil; Khadka, Anjan; Brashier, Dick S.; Gupta, A. K.; Sharma, A. K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Paracetamol is used for symptomatic treatment of fever and pain with isoniazid and other anti-tubercular drugs in patients of tuberculosis. Literature has conflicting data regarding their interaction. Some studies show that isoniazid increases oxidative metabolism of paracetamol whereas some other suggest that isoniazid has an inhibitory effect. The present study was conducted to find out the possible interaction between paracetamol and isoniazid. Methods: The study was undertaken on Wistar strain of Albino rats. Group I and Group II animals were treated with paracetamol (500 mg/kg) and the combination of paracetamol (500 mg/kg) and isoniazid (30 mg/kg) respectively for 2 months. Blood samples were taken before and during the study for biochemical and histopathological studies of liver and renal functions and plasma paracetamol concentration was also evaluated. Results: Isoniazid decreased the plasma paracetamol concentration without affecting its analgesic activity. However, the hepatotoxic and nephrotoxic effects of paracetamol were found to be further aggravated by isoniazid co-administration. Conclusion: Isoniazid potentiates the hepatotoxic and nephrotoxic effects of paracetamol possibly due to hepatic enzyme induction by isoniazid.